UPAYA MENINGKATKAN MOTIVASI BELAJAR SUB KETERAMPILAN BERKOMUNIKASI MELALUI LAYANAN PENGUASAAN KONTEN DENGAN TEKNIK PERMAINAN PADA SISWA KELAS XII.IPA.3 DI SMAN 1 PASAMAN - Syofyan, Syofyan (STKIP Pesisir Selatan, 2018)
Taking into account the expectations to be achieved for the school organizers through optimum student coaching both academic and non academic potential, is the education process must produce human noble character, noble character, superior personality, leadership, entrepreneur, patriot soul, soul of innovator, initiative, creative and independent. Facts that occur in the field of problems learning motivation sub skill communicating students that occurred in SMAN 1 Pasaman be the responsibility of teachers in the school counseling through guidance and counseling services. This research is a service action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. The population in this study is all students of Class XII.IPA.3 in SMAN 1 Pasaman, which consists of 30 students. The results showed that the average of students' learning motivation sub skill experienced an increase of 8.76%. Motivation to learn sub skill communicate student before executed service mastery of content with game technique, show medium category that is 62,37%. Motivation to learn sub skill communicating student after implemented service mastery of content with game technique, showing medium category that is 71,13%. Based on the description, it can be concluded there is an increase in motivation to learn sub-communication skills through content mastery services with game techniques on Students Class XII.IPA.3 at SMAN 1 Pasaman Year Teaching 2015/2016